Advances in questionnaire design, development, evaluation and testing - Beatty, Paul C. (John Wiley & Sons, Ltd., 2019)
"Building on the success of the volume from the first Questionnaire Development, Evaluation, and Testing (QDET) conference edited by Stanley Presser (Wiley, 2004), this book brings together international experts in survey methodology in one volume to publish the results of the first conference in over a decade on questionnaire design and evaluation (QDET-2). The dramatic expansion of electronic and self-administered surveys since that time has led to a need for greater guidance on the design and evaluation of instruments relying upon these modes. It will also move beyond recent emphasis on academic and government research, to incorporate more approaches derived from the commercial sector. Methodologists have worked actively on optimal approaches for the development and evaluation of modern survey instruments, but such information has not been systematically disseminated in one forum that brings together various stakeholders in survey quality. This book, edited by leaders in the field, provides an opportunity to organize chapters into a cohesive unit that points to new directions for research and guides an emerging generation of methodologists. The book is a proactive forum to prepare researchers to meet the next generation of challenges, making it of interest to both researchers and practitioners internationally in government, academia, and the private sector"--